Possible Antiviral Activity of 5-Aminolevulinic Acid in Feline Infectious Peritonitis Virus (Feline Coronavirus) Infection - Takano, Tomomi; Satoh, Kumi; Doki, Tomoyoshi (Frontiers in Veterinary Science, 2021)
Feline infectious peritonitis (FIP) is a life-threatening infectious disease of cats caused by virulent feline coronavirus (FIP virus: FIPV). For the treatment of FIP, several effective antivirals were recently reported, but many of these are not available for practical use. 5-amino levulinic acid (5-ALA) is a low-molecular-weight amino acid synthesized in plant and animal cells. 5-ALA can be synthesized in a large amount, and it is widely applied in the medical and agricultural fields. We hypothesized that 5-ALA inhibits FIPV multiplication. Therefore, we evaluated its antiviral activity against FIPV in felis catus whole fetus-4 cells and feline primary macrophages. FIPV multiplication was significantly inhibited by 250 µM 5-ALA. Our study suggested that 5-ALA is applicable for the treatment and prevention of FIPV infection.